2015
DOI: 10.1016/j.jaging.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding welfare conditionality in the context of a generational habitus: A qualitative study of older citizens in England

Abstract: HighlightsOlder adults in England narrated experiences as generational.'Our generation' was characterised as having struggled to achieve self-reliance Receipt of universal age-related benefits was congruent with generational habitus Means and needs based conditionality fostered discourses of differentiation.Increasing conditionality may promote division within and between generations 3 Understanding welfare conditionality in the context of a generational habitus: a qualitative study of older citizens in Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We identified many reasons why participants did not seek assistance from services —many of which have been described in the literature [ 4 , 5 ]—but uniquely, we combine these with participants’ reasons for not pursuing assistance from other sources . The literature suggests that older people’s desire to preserve an independent, self-reliant, responsible self-image can deter assistance-seeking from outside the household [ 6 , 9 , 20 ]. Like others [ 21 ], we found that preparedness to receive assistance depended to some extent on participants’ notion of independence: assistance remained unpalatable while they could remain independent without it, but this view shifted where they perceived that independence could be achieved through assistance.…”
Section: Discussionmentioning
confidence: 99%
“…We identified many reasons why participants did not seek assistance from services —many of which have been described in the literature [ 4 , 5 ]—but uniquely, we combine these with participants’ reasons for not pursuing assistance from other sources . The literature suggests that older people’s desire to preserve an independent, self-reliant, responsible self-image can deter assistance-seeking from outside the household [ 6 , 9 , 20 ]. Like others [ 21 ], we found that preparedness to receive assistance depended to some extent on participants’ notion of independence: assistance remained unpalatable while they could remain independent without it, but this view shifted where they perceived that independence could be achieved through assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since old age is not a socially homogenous category, it is important to grasp the effect that different ways of life bear on the generational habitus (Gilleard and Higgs , Milton et al . ) regarding individuals’ therapeutic cultures (Lopes et al . ).…”
Section: Introductionmentioning
confidence: 99%